Land-based reflection: sitting with the lake - Soto, Venessa (My University, 2026)
This piece explores a land-based reflection grounded in relationality, memory, and Indigenous ways of knowing. Through a place study conducted at a lakeside environment, the work documents a two-hour experience of sitting with the land, observing both human and more than human relationship's, and engaging in intentional stillness. Intentional stillness initially shaped by restlessness and distraction, the experience gradually shift toward presence, as the body and mind begin to attune to the rhythms of the natural world. Drawing on Marcus (2023) and Gaudet (2019), this reflection is guided by the concepts of auto-geography and keenoukaywin, or "the visiting way." The land is understood not as a passive setting, but as a living relation layered with histories, meanings, and teachings. Personal memories of family, particularly those connected to intergenerational practices of visiting, storytelling, and gathering, emerge as central to understanding the deeper significance of place. These memories are not separate from the land, but are carried within it, reinforcing the interconnectedness between identity, story, and environment. The work highlights how visiting the land parallels visiting relatives, requiring respect, attentiveness, and reciprocity. Through sensory engagement and reflection, the experience becomes one of reconnection, both with the land and with inherited teachings that emphasize responsibility to all relations. This piece contributes to ongoing conversations in early childhood education by emphasizing the importance of land-based learning and relational pedagogies that extend beyond human-centered frameworks.
Keywords: Relationality; presence; place-based reflection